Relative Impact of Infrastructural Provision by CBOs in Akure South LGA of Ondo State, Nigeria: Application of Facility Contributory Index - Emmanuel, Adebayo Adewunmi (Richtmann Publishing, 2012)
Infrastructural provision is a catalyst for economic development at various levels. The influence on local economicdevelopment and the alleviation of poverty is unquantifiable. In some instances, CBOs embark on physical development projectsto provide facilities in their communities. This paper exposes the relative impact of facilities provided by CBOs in Akure SouthLocal Government Area of Ondo State, Nigeria on the economy of residents. 262 respondents of the LGA which were selectedby stratified random sampling provided information through a questionnaire to reveal the degree of contribution of certain 10facilities to their personal economy. Facility Contributory Index (FCI) model was developed using likert’s scale to determinevarious levels of contribution of the facilities. It was discovered among other things that Health related facilities ranked highest onthe FCI Table of assessment while recreational facilities remain the least contributor due to low provision coupled with degree ofcontribution. Recommendations include a policy overhaul to establish partnership between government and NPOs in order tostimulate efforts of CBOs in local communities.